Novel Bi-Allelic Variants of FANCM Cause Sertoli Cell-Only Syndrome and Non-Obstructive Azoospermia - Zhang, Yuxiang; Li, Peng; Liu, Nachuan; Jing, Tao; Ji, Zhiyong; Yang, Chao; Zhao, Liangyu; Tian, Ruhui; Chen, Huixing; Huang, Yuhua; Zhi, Erlei; Ou, Ningjing; et al. (Frontiers in Genetics, 2021)
Non-obstructive azoospermia (NOA) is the most severe disease in male infertility, but the genetic causes for majority of NOA remain unknown. FANCM is a member of Fanconi Anemia (FA) core complex, whose defects are associated with cell hypersensitivity to DNA interstrand crosslink (ICL)-inducing agents. It was reported that variants in FANCM (MIM: 609644) might cause azoospermia or oligospermia. However, there is still a lack of evidence to explain the association between different FANCM variants and male infertility phenotypes. Herein, we identified compound heterozygous variants in FANCM in two NOA-affected brothers (c.1778delG:p.R593Qfs*76 and c.1663G>T:p.V555F) and a homozygous variant in FANCM (c.1972C>T:p.R658X) in a sporadic case with NOA, respectively. H&E staining and immunohistochemistry showed Sertoli cell-only Syndrome (SCOS) in the three patients with NOA. Collectively, our study expands the knowledge of variants in FANCM and provides a new insight to understand the genetic etiology of NOA.